Southeast Asia in search of an ASEAN community insights from the former ASEAN secretary-general - Severino, Rodolfo (Singapore Institute of Southeast Asian Studies, 2006)
"... This volume reappraises the organization from the inside, through controversial or perplexing issues such as the "ASEAN Way", the accession of the new members, including Myanmar, the principle of "non-interference", regional security, regional economic integration, the haze and SARS, and ASEAN's future"--ISEAS Publications Unit.
1. The "ASEAN way": its name and origins -- 2. Who belongs in ASEAN? The question of membership -- 3. The issue of non-interference -- 4. Regional security: the ASEAN role -- 5. Integrating the regional economy -- 6. ASEAN and the world -- 7. The ASEAN community: is it for real? -- 8. What kind of future for ASEAN?
Maps on lining papers.
Includes bibliographical references and index.
Keywords: ASEAN; National security -- Southeast Asia; Regionalism -- Southeast Asia; Southeast Asia -- Economic integration; Southeast Asia -- Foreign economic relations; Southeast Asia -- Politics and government -- 1945-.